Hydrostatically loaded structures : the structural mechanics, analysis, and design of powered submersibles - Nash, William A. (Pergamon, 1995)
Powered submersibles have enabled the exploration of lake and ocean depths, and are used extensively for inspection of drilling rigs and offshore pipelines. Their potential for the discovery of undersea mineral resources is widely acknowledged. The design of such vehicles poses many problems not encountered with land-based systems: for example, normal pressures are very large, and many structural elements are extremely sensitive to initial geometric imperfections. Following a review of the history and development of submersibles, each chapter concentrates on a specific geometric design. The bibliography is unusually complete, and includes summaries of many referenced publications. This unique book covers all aspects of the structural mechanics, analysis and design of submersibles, and will be invaluable to ocean engineers, naval architects and graduate students entering the field.